2021
DOI: 10.1002/marc.202100192
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization of Step‐/Chain‐Growth and Radical/Cationic Polymerizations Using Thioacetals as Key Components for Triblock, Periodic and Random Multiblock Copolymers with Thermoresponsiveness

Abstract: A novel strategy for synthesizing a series of multiblock copolymers is developed by combining radical/cationic step‐growth polymerizations of dithiols and divinyl ethers and chain‐growth cationic degenerative chain‐transfer (DT) polymerizations of vinyl ethers using thioacetals as key components. The combination of radical step‐growth polymerization and a cationic thiol‐ene reaction or cationic step‐growth polymerization enables the synthesis of a series of macro chain‐transfer agents (CTAs) composed of poly(t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…32 After these preliminary studies, PDTA synthesis has been overlooked for a long time, but it has started to attract attention again in the last decade in parallel with the developments in polymer science. [33][34][35][36][37][38] More recently, Yang and coworkers reported monomer-polymer recycling of PDTA. 39 The authors prepared PDTA from 3,4,5-trimethoxybenzaldehyde and a variety of alkyl dithiols in acetonitrile catalyzed by p-toluenesulfonic acid (PTSA) at 50 °C for 24 h. Next, the authors described that the PDTA showed depolymerizability via ring-closing depolymerization into macrocycles, followed by entropy-driven ring-opening polymerization to reassemble the pristine PDTAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 After these preliminary studies, PDTA synthesis has been overlooked for a long time, but it has started to attract attention again in the last decade in parallel with the developments in polymer science. [33][34][35][36][37][38] More recently, Yang and coworkers reported monomer-polymer recycling of PDTA. 39 The authors prepared PDTA from 3,4,5-trimethoxybenzaldehyde and a variety of alkyl dithiols in acetonitrile catalyzed by p-toluenesulfonic acid (PTSA) at 50 °C for 24 h. Next, the authors described that the PDTA showed depolymerizability via ring-closing depolymerization into macrocycles, followed by entropy-driven ring-opening polymerization to reassemble the pristine PDTAs.…”
Section: Introductionmentioning
confidence: 99%
“…42,43 Therefore, PDTAs have found extensive applications in bio-related fields where controlled degradation is desired, such as targeted drug delivery and tissue engineering. 26,37,[44][45][46][47][48][49][50] In particular, all these recent studies indicate the huge potential and the increasing importance of PDTA in terms of synthetic polymer chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we previously reported that main‐chain thioacetal bonds of polythioacetals, which are prepared by step‐growth cationic thiol‐ene polymerization of dithiol and divinyl ether, can serve as macro‐chain‐transfer agents for cationic polymerization of vinyl ethers to form copolymers. [ 82 , 83 ] However, the total polymer chain lengths cannot be controlled due to the step‐growth mechanism for the formation of polythioacetals in the first step.…”
Section: Introductionmentioning
confidence: 99%
“…However, trithiocarbonate bonds are labile and can generate products with color and odor. In addition, we previously reported that main‐chain thioacetal bonds of polythioacetals, which are prepared by step‐growth cationic thiol‐ene polymerization of dithiol and divinyl ether, can serve as macro‐chain‐transfer agents for cationic polymerization of vinyl ethers to form copolymers [82, 83] . However, the total polymer chain lengths cannot be controlled due to the step‐growth mechanism for the formation of polythioacetals in the first step.…”
Section: Introductionmentioning
confidence: 99%